Effectiveness of the Educational Technology “Sophia’s Story” in Transitional Care and Stimulation of Preterm Infants - Jamile Gregorio Morelo; Pamela Brustolini Oliveira Rena; Rayla Amaral Lemos; Nádia Proença de Melo; Maria de La Ó Ramallo Veríssimo (Revista Brasileira de Enfermagem)
ABSTRACT Objectives: to evaluate the effectiveness of the educational technology “Sophia’s Story: Battles and Triumphs of the Family in the Care and Development of the Premature Child” in promoting home-based stimulation for preterm infants and to assess associations between family, demographic, and behavioral factors and the promotion of home-based stimulation for preterm infants. Methods: a pragmatic, non-randomized clinical trial was conducted with 35 preterm infants discharged from the neonatal intensive care unit in each group, approved by a Research Ethics Committee. Caregivers received standardized hospital discharge guidance, with the educational technology provided to the experimental group. Home-based stimulation was assessed using the Infant-Toddler Home. Results: the experimental group obtained higher scores in the overall mean (p=0.001) and in the following subscales: absence of punishment and restriction (p=0.005); availability of materials, toys, and appropriate games (p=0.001); maternal involvement with the child (p=0.001); and opportunity for variation in daily stimulation (p=0.025). Conclusions: exposure to the educational technology resulted in greater home-based stimulation, supporting transitional care.